Pattern search algorithm based automatic online parameter estimation for AGC with effects of wind power. (January 2017) - Suresh Kumar, L.V.; Nagesh Kumar, G.V.; Madichetty, Sreedhar
Highlights: IEEE 39 Bus system with 10 generators is executed with three wind generators. Automatically computes the gain parameters for different load variations. Small signal model of WE system was modelled with IEEE-39 bus system. Different case studies and test cases has been performed; (SLP-10% and 20%), (GRC-3% and 10%). Also a case study has to be performed for various step load for turbulence (1%, 3% & 10%). Abstract: The increasing portion of wind energy in the power system puts forward stability challenges to the power grid. With introduction of wind generating systems, maintaining constant frequency became one of the important problems taking stability into account. The system could be maintained with constant frequency with the help of controllers. The controller gains are usually designed with fixed values for various scenarios of power system which considerably vague due to existing system complexity. Also, the usage of conventional techniques consumes a lot of computational time and does not possesses accurate control gain parameters. To address the aforementioned challenges, an automatic online gain estimation algorithm by using pattern search optimization technique has been proposed in this article. This method computes the parameters on its own based on variable wind power output and controller gains will adjust automatically to achieve the best desired performance. The proposed method was tested in a modified IEEE 39 bus system for scenarios like system with 3% and 10% GRC (Generator Rate Constraint) with 10% and 20% SLP (Step Load Perturbation). Following that the system with proposed method was investigated with variable wind power and results demonstrate significant better results which comply with IEEE standards.